BF3‐induced reversible covalent organic framework radicals - Shiwei Zhang; Xin Wang; Fangyuan Kang; Qianfeng Gu; Guohan Sun; Yung‐Kang Peng; Qichun Zhang (SmartMat, 2024)
Abstract The integration of radials into covalent organic frameworks (COFs) would have a profound effect on their applications in spin devices since such radical arrays can offer scientists an additional dimension to manipulate electron spins and maximize the function of organic optoelectrical devices. However, such realization (especially reversible radicals) is very challenging. In this article, using a fluorene‐based benzoquinone‐derived monomer (M) as the building unit, we successfully synthesized a boroxine‐linked COF (named CityU‐3), whose crystallinity and chemical composition were confirmed by powder X‐ray diffraction (PXRD), Fourier‐transform infrared (FT‐IR) spectroscopy, solid‐state 13C cross‐polarization magic‐angle‐spinning (CP/MAS) NMR, and X‐ray photoelectron spectroscopy (XPS). Interestingly, CityU‐3 can be converted into its radical form by treating with BF3·Et2O, which is associated with a color change from red to black, and vice versa upon heating. The as‐formed radicals have been confirmed by electron paramagnetic resonance (EPR) spectroscopy. It is worth pointing out that the cycles between radical formation and disappearance would not affect its crystallinity and structure. The reversible COF radicals would have great applications in organic spin devices.